Salmoneus durisi sp. nov., an infaunal alpheid shrimp probably associated with callianassid ghost shrimps in the tropical Indo-West Pacific (Malacostraca: Decapoda: Caridea) - Anker, Arthur; Ashrafi, Hossein (Zootaxa, 2019)
A new species of the alpheid shrimp genus Salmoneus Holthuis, 1955, probably an obligate associate of ghost shrimp burrows, is described based on material from Oman (type locality: Darsait near Muscat), Iran and the Philippines. Salmoneus durisi sp. nov. is characterised principally by both chelipeds enlarged, robust, with ventral and dorsal margins of chelae carrying long fine setae, and with minor chela fingers armed with a few large teeth on cutting edges. All specimens of Salmoneus durisi sp. nov. were collected either directly from burrows of larger decapod crustaceans with the aid of a suction pump, or by exposing burrows dug under large subtidal rocks. The Iranian specimen was found together with its presumed host, Neocallichirus calmani (Nobili, 1904). Two additional specimens from Indonesia and the Solomon Islands are tentatively assigned to S. cf. durisi sp. nov., awaiting further studies.